Virus-associated ribozymes and nano carriers against COVID-19 - Donmus, Beyza; Unal, Sinan; Kirmizitas, Fatma Ceren; Lacin, Nelisa Turkoglu (TAYLOR & FRANCIS LTD, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a zoo tonic, highly pathogenic virus. The new type of coronavirus with contagious nature spread from Wuhan (China) to the whole world in a very short time and caused the new coronavirus disease (COVID-19). COVID-19 has turned into a global public health crisis due to spreading by close person-to-person contact with high transmission capacity. Thus, research about the treatment of the damages caused by the virus or prevention from infection increases everyday. Besides, there is still no approved and definitive, standardized treatment for COVID-19. However, this disaster experienced by human beings has made us realize the significance of having a system ready for use to prevent humanity from viral attacks without wasting time. As is known, nanocarriers can be targeted to the desired cells in vitro and in vivo. The nano-carrier system targeting a specific protein, containing the enzyme inhibiting the action of the virus can be developed. The system can be used by simple modifications when we encounter another virus epidemic in the future. In this review, we present a potential treatment method consisting of a nanoparticle-ribozyme conjugate, targeting ACE-2 receptors by reviewing the virus-associated ribozymes, their structures, types and working mechanisms.
Keywords: Coronaviruses; COVID-19; ribozyme; nanocarrier; targeting; LONG-TERM STORAGE; RNASE-P; HAIRPIN RIBOZYME; GENE-THERAPY; IN-VITRO; NANOPARTICLES; DELIVERY; INHIBITION; CANCER; SIRNA; Biotechnology & Applied Microbiology; Engineering; Materials Science